Environment-friendly floating buoy and preparation method thereof
By combining polycarbonate with high-density polyethylene, low-density polyethylene, carbon fiber and other components and filling with foamed polystyrene, a biodegradable floating float can be prepared, which solves the easy damage and buoyancy failure of the floating float can be achieved at sea. The problem of improving performance and environmental protection.
Patent Information
- Application Number
- CN202411392947.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-07
AI Technical Summary
In offshore applications, existing floating floats are susceptible to damage caused by external environmental impacts such as waves, resulting in buoyancy failure and damage to marine organisms, and are difficult to biodegrade.
Polycarbonate is used to combine with high-density polyethylene, low-density polyethylene, carbon fiber and other components to prepare a hollow float shell through specific transesterification and melt extrusion processes, and fill the shell with foamed polystyrene. Improve the mechanical properties and biodegradability of the float.
It significantly improves the mechanical properties and biodegradability of the float, reduces damage to marine organisms, and solves the problem of buoyancy failure. It has simple process, low cost and environmentally friendly significance.
Smart Images

Figure CN119264539A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of buoys, and in particular to an environmentally friendly floating buoy and a preparation method thereof. Background Art
[0002] It is undoubtedly a major trend to vigorously develop environmentally friendly clean energy and further reduce the consumption of traditional energy in the future. Clean energy on water and sea, especially floating photovoltaic projects, has gradually become the focus of energy transformation due to its unique natural environment advantages (such as less obstruction, long sunshine time and reflective light on the water surface, etc.) and its wider application range and larger laying area. Therefore, in order to ensure the long-term safe and stable implementation of the project, the design of the floating pontoon is crucial.
[0003] At present, polyethylene buoys are recognized as floating materials with qualified performance at home and abroad, and there have been many successful cases of floating photovoltaic power stations on the water. However, unlike ordinary water environments, offshore applications are more complicated and frequently subjected to external environmental impacts such as waves, making them prone to damage. On the one hand, when there are gaps or cracks in the buoy, seawater enters the cavity, causing buoyancy failure and causing huge economic losses; on the other hand, the broken structures of the buoys such as fragments and broken shells produced by the damage of the buoys pose a safety hazard to marine life. When these broken structures of the buoys are entangled or stuck on marine life, they cause great pain and harm to marine life, causing irreversible damage to marine life.
[0004] On the premise of ensuring the good performance of the buoy, how to improve the biodegradability of the buoy and reduce the damage to marine life caused by the buoy when it is broken after long-term use is a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of the above problems, the present invention provides an environmentally friendly floating pontoon and a preparation method thereof, with the aim of providing a floating pontoon with better biodegradability and excellent performance.
[0006] In one aspect, the present invention provides an environmentally friendly floating buoy, comprising a buoy shell and a filling body filled in the buoy shell; wherein the buoy shell comprises the following components in parts by weight:
[0007]
[0008] The structural formula of the polycarbonate is 8≤m≤16.
[0009] Optionally, the weight average molecular weight of the polycarbonate is 40,000 to 50,000, and the molecular weight distribution coefficient is 0.6 to 0.8.
[0010] Optionally, the ratio of the weight fraction of the polycarbonate to the total weight fraction of the high-density polyethylene and the low-density polyethylene is (42-45):100.
[0011] Optionally, the density of the high-density polyethylene is 0.945-0.97 g / cm 3 , melt index is 4-10g / 10min;
[0012] The density of the low-density polyethylene is 0.91-0.94 g / cm 3 , the melt index is 30-50g / 10min.
[0013] Optionally, the carbon fiber is a composite carbon fiber, which comprises carbon fiber, nano-silica, carbon black, talcum powder and a silane coupling agent.
[0014] Optionally, the mass ratio of nano-silicon dioxide, carbon black, talcum powder and silane coupling agent in the composite carbon fiber is (0.5-5):(0.5-5):(0.1-3):(1-5);
[0015] The carbon fiber has a length of 1 to 10 mm, preferably 4 to 8 mm, and a diameter of 1 to 10 μm, preferably 2 to 8 μm.
[0016] Optionally, the antioxidant is selected from at least one of antioxidant 168, antioxidant 1010, and antioxidant 1076;
[0017] The ultraviolet absorber is selected from at least one of UV-328, UV-329 and UV-327;
[0018] The light stabilizer is selected from at least one of light stabilizer 770, light stabilizer 944, and light stabilizer 2020;
[0019] The dispersant is selected from at least one of vinyl bisstearamide, calcium stearate, and oxidized polyethylene wax.
[0020] Optionally, the filler is expanded polystyrene;
[0021] The thickness of the buoy shell is 2 to 5 cm;
[0022] When the buoy shell is cylindrical, the ratio of height to diameter is 1-2:1, the height is 30-70 cm, and the diameter is 10-40 cm.
[0023] In another aspect, the present invention provides a method for preparing the above-mentioned environmentally friendly floating buoy, which comprises the following steps:
[0024] (1) Diphenyl carbonate and alkyl glycol HO-(CH2) m-OH is prepolymerized and transesterified in the presence of a catalyst to obtain polycarbonate 8≤m≤16;
[0025] (2) The following components in parts by weight are sequentially melted, plasticized, extruded, granulated, and processed into a hollow buoy shell:
[0026]
[0027] (3) Filling a filling body inside the buoy shell to obtain the environmentally friendly floating buoy.
[0028] Optionally, steps (1) to (3) are performed as follows:
[0029] In step (1):
[0030] The alkyl glycol is 1,12-dodecanediol;
[0031] The catalyst is a phosphazene-based catalyst, preferably t-BuP2;
[0032] The weight ratio of the diphenyl carbonate, the alkyl glycol and the catalyst is 100:(105-110):(0.001-0.002);
[0033] The prepolymerization comprises:
[0034] The diphenyl carbonate and the alkyl glycol are dissolved in tetrahydrofuran under vacuum, and then the catalyst is added and stirred at a constant temperature of 80 to 90° C. and a speed of 10 to 15 r / min for 2 to 4
[0035] h, to obtain a prepolymerized product;
[0036] The transesterification comprises:
[0037] The prepolymer product is heated to 200-230° C. and subjected to reduced pressure distillation reaction for 10-12 hours, and then separated by sedimentation with n-hexane and then dried in vacuum to obtain the polycarbonate;
[0038] In step (2):
[0039] The hollow buoy shell is processed by blow molding;
[0040] In step (3):
[0041] The filling body is filled in the buoy shell by a pouring method or a spraying method.
[0042] Beneficial effects:
[0043] (1) The present invention uses a specific polycarbonate compounded with high-density polyethylene, low-density polyethylene, carbon fiber and other components and evenly distributed in the buoy shell, so that the buoy shell has excellent mechanical properties, environmental stress resistance and other properties, and its biodegradability is greatly improved. When the buoy is damaged, the direct harm to marine life is greatly reduced, thus avoiding irreversible damage to marine life;
[0044] (2) The inner cavity of the buoy shell is filled with expanded polystyrene, which solves the buoyancy failure problem of the offshore floating buoy. The production process is simple, the production efficiency is high, the cost is low, the material is easy to obtain, and it has extremely high environmental value. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is a structural schematic diagram of a specific implementation mode of the environmentally friendly floating buoy provided by the present invention;
[0046] Figure 2 is a reaction route diagram for preparing polycarbonate according to the present invention;
[0047] Figure 3 is a SEM photograph of the composite carbon fiber prepared in the composite carbon fiber preparation example 1 of the present invention;
[0048] Description of Reference Numerals
[0049] 1 diphenyl carbonate; 2 alkyl glycol; 3 phenol;
[0050] 4 Polycarbonate; 5 Float shell; 6 Filling body. DETAILED DESCRIPTION
[0051] The present application is further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present application will become clearer and more specific.
[0052] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.
[0053] In this application, the terms "optional", "optional" or "optionally" mean that the subsequently described event or circumstance may or may not occur, and the description includes the occurrence of the event or circumstance and the non-occurrence of the event or circumstance.
[0054] In addition, the technical features involved in different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0055] In one aspect, the present invention provides an environmentally friendly floating buoy, such as Figure 1As shown, it includes a buoy shell 5 and a filling body 6 filled in the buoy shell; wherein the buoy shell 5 contains the following components in parts by weight:
[0056]
[0057] The structural formula of the polycarbonate is 8≤m≤16.
[0058] Firstly, the buoy shell of the present invention comprises high-density polyethylene, low-density polyethylene, carbon fiber, antioxidant, ultraviolet absorber, light stabilizer, etc. The high-density polyethylene, low-density polyethylene and carbon fiber are compounded according to the above-mentioned weight proportions so that the buoy shell has excellent mechanical properties; at the same time, the antioxidant, light stabilizer and ultraviolet absorber can improve the anti-oxidation and ultraviolet resistance of high-density polyethylene and low-density polyethylene, so that the floating buoy can be used for offshore photovoltaics.
[0059] Secondly, the buoy shell of the present invention also includes polycarbonate, and the ester bond can be completely degraded in the body. The ester bond is hydrolyzed by carboxylesterase in the body, resulting in a decrease in molecular weight, and gradually degraded into oligomers. As the degradation proceeds, there will be more and more carboxyl groups inside the material to accelerate the degradation of the internal material, further increasing the difference between the inside and the outside. When the internal material is completely transformed into a soluble oligomer and dissolved in an aqueous medium, it can be absorbed by the organism or excreted from the body. The introduction of polycarbonate into the buoy shell of the present invention greatly improves its biodegradability, avoiding irreversible damage to marine organisms.
[0060] Furthermore, the buoy shell of the present invention comprises the above-mentioned components such as polycarbonate, high-density polyethylene, low-density polyethylene, carbon fiber, etc., and the above-mentioned multiple components are evenly distributed in the buoy shell. When the buoy is damaged after being used for a long time floating on the sea, the buoy shell mainly composed of high-density polyethylene, low-density polyethylene, carbon fiber and polycarbonate can be damaged into a smaller structure due to the presence of carbon fiber and polycarbonate, thereby avoiding the long-term existence of a large-volume damaged shell structure, greatly reducing the situation where the damaged shell structure is entangled or stuck on marine life, and greatly reducing the direct damage to marine life. Furthermore, the amount of high-density polyethylene and low-density polyethylene used in the buoy shell of the present invention is greatly reduced compared to the pure polyethylene shell, and the impact of the buoy shell particles finally formed on the environment is also greatly reduced.
[0061] In one embodiment of the environmentally friendly floating buoy of the present invention, the weight average molecular weight of the polycarbonate is 40,000 to 50,000, and the molecular weight distribution coefficient is 0.6 to 0.8.
[0062] It should be noted that by compounding polycarbonate that meets the above-mentioned weight average molecular weight and molecular weight distribution coefficient with components such as high-density polyethylene, low-density polyethylene, and carbon fiber, the buoy shell has excellent mechanical properties and buoyancy, and the polycarbonate has good biodegradability.
[0063] In another embodiment of the environmentally friendly floating pontoon of the present invention, the weight ratio of the polycarbonate to the total weight of the high-density polyethylene and the low-density polyethylene is (42-45):100.
[0064] It should be noted that by controlling the weight ratio of polycarbonate to the total weight of high-density polyethylene and low-density polyethylene as above, the buoy shell has better mechanical properties, can float on the water more stably, and has excellent biodegradability.
[0065] In one embodiment of the environmentally friendly floating buoy of the present invention, the density of the high-density polyethylene is 0.945-0.97 g / cm 3 , melt index is 4-10g / 10min;
[0066] The density of the low-density polyethylene is 0.91-0.94 g / cm 3 , the melt index is 30-50g / 10min.
[0067] It should be noted that in the buoy shell system of the present invention, the mechanical properties of the buoy shell are further improved by compounding other components with high-density polyethylene and low-density polyethylene with the above-mentioned density and melt index, and the degradation time of the damaged particles finally formed after the buoy shell is damaged is shorter than that of the buoy shell formed by a single polyethylene resin by compounding these two polyethylenes.
[0068] In a preferred embodiment of the above-mentioned environmentally friendly floating buoy of the present invention, the carbon fiber is a composite carbon fiber, and the composite carbon fiber comprises carbon fiber, nano-silica, carbon black, talc and a silane coupling agent.
[0069] It should be noted that the above-mentioned composite carbon fiber is preferably prepared by a method comprising the following steps:
[0070] (S1) treating the carbon fiber surface with a vacuum plasma cleaning machine to obtain surface activated carbon fiber; (S2) grinding the filler and filtering through a sieve to obtain filler powder; wherein the filler comprises nano-silicon dioxide, carbon black and talcum powder;
[0071] (S3) mixing filler powder, silane coupling agent and solvent and dispersing the mixture by ultrasonication to obtain an impregnation solution;
[0072] (S4) treating the surface activated carbon fiber obtained in step (S1) with ultrasonic vibration in the impregnation solution obtained in step (S3) and then vacuum drying to obtain the composite carbon fiber.
[0073] In the above method for preparing composite carbon fiber, when the surface treatment is performed in step (S1), the gas used in the above vacuum plasma cleaning machine can be oxygen, the radio frequency frequency can be 25-30KHz, the power can be 60-80%, the pressure in the cavity can be 100-120Pa, and the oxygen flow rate can be 3-7cm 3 / min, the processing time can be 3 to 5 minutes.
[0074] In the above method for preparing composite carbon fiber, the mass ratio of carbon fiber in step (S1), nano-silicon dioxide, carbon black, talcum powder in step (S2), and silane coupling agent in step (S3) can be 100: (0.5-5): (0.5-5): (0.1-3): (1-5). The above silane coupling agent can be silane coupling agent KH550, the sieve in step (S2) can be 400-600 mesh, and the solvent in step (S3) can be anhydrous ethanol. When preparing the impregnation solution in step (S3), the mass ratio of the filler powder, the silane coupling agent and the solvent can be (2-6): (0.5-3): (100-150). When the ultrasonic oscillation treatment is performed in step (S4), the mass ratio of the impregnation solution to the surface activated carbon fiber can be 1-2:1, and the time of the ultrasonic oscillation treatment can be 1-2h.
[0075] In the above-mentioned method for preparing composite carbon fiber, in step (S1), active groups such as hydroxyl and carboxyl are formed on the surface of the carbon fiber through plasma treatment, and then through steps (S2) to (S4), nano-silica, carbon black and talcum powder are compounded to the surface of the carbon fiber, or compounded to the surface of the carbon fiber through a silane coupling agent, especially the alkyl (R) group of the silane coupling agent faces outward and can better blend with organic phase components such as high-density polyethylene and low-density polyethylene to form a buoy shell with better stability.
[0076] In one embodiment of the above-mentioned environmentally friendly floating buoy of the present invention, the mass ratio of nano-silicon dioxide, carbon black, talcum powder and silane coupling agent in the composite carbon fiber is (0.5-5):(0.5-5):(0.1-3):(1-5);
[0077] The carbon fiber has a length of 1 to 10 mm, preferably 4 to 8 mm, and a diameter of 1 to 10 μm, preferably 2 to 8 μm.
[0078] It should be noted that when the length of carbon fiber is too long, it is not conducive to the molding of composite carbon fiber. Conversely, when the length is too short, the strength of the composite carbon fiber is weak. By controlling the length and diameter of the carbon fiber as above, and controlling the mass ratio of nano-silica, carbon black, talcum powder, and silane coupling agent as above, the composite carbon fiber can better exert its function, and the buoy shell has excellent mechanical properties while maintaining good biodegradability.
[0079] In the above-mentioned composite carbon fiber, nano-silicon dioxide, carbon black, and talcum powder can be connected to the carbon fiber through a silane coupling agent, wherein the alkyl (R) group of the silane coupling agent faces outward, and the composite carbon fiber becomes oleophilic and hydrophobic, and is easier to mix with high-density polyethylene and low-density polyethylene, thus improving the disadvantage that the organic phase of high-density polyethylene and low-density polyethylene and the inorganic dispersed phase of carbon fiber are difficult to combine. Figure 3 As shown, the fibers in the composite carbon fiber are intertwined to form a fiber network, and the "island structure" formed by nano-silicon dioxide, carbon black, and talcum powder can be distributed at the positions where the fibers are intertwined.
[0080] Nano-silica, carbon black, and talc in the "island structure" composite carbon fiber use the high specific surface area characteristics of carbon fiber to adsorb on the surface of carbon fiber, and then further mix with high-density polyethylene and low-density polyethylene, solving the incompatibility and local agglomeration problems of traditional inorganic fillers and organic phases, thereby giving full play to their advantages and enhancing and modifying high-density polyethylene and low-density polyethylene. While nano-silica, carbon black, and talc improve mechanical properties, carbon black and nano-silica can also be used as ultraviolet absorbers to improve the photo-oxidation aging properties of high-density polyethylene and low-density polyethylene.
[0081] The "island structure" composite carbon fiber can effectively disperse external stress stimulation and improve the impact resistance and environmental stress cracking resistance of high-density polyethylene and low-density polyethylene. The "island structure" composite carbon fiber is further fused with high-density polyethylene and low-density polyethylene under the action of a coupling agent. As a dispersed network with carbon fiber as the main skeleton, it plays the role of a stress concentration point. That is, when stimulated by external forces, the tip stress of the crack extension will be released by the synergistic effect of the relatively soft composite carbon fiber and dispersed phase particles, thereby improving the impact resistance and stress cracking resistance of high-density polyethylene and low-density polyethylene.
[0082] In one embodiment of the above-mentioned environmentally friendly floating buoy of the present invention, the antioxidant is selected from at least one of antioxidant 168, antioxidant 1010, and antioxidant 1076;
[0083] The ultraviolet absorber is selected from at least one of UV-328, UV-329 and UV-327;
[0084] The light stabilizer is selected from at least one of light stabilizer 770, light stabilizer 944, and light stabilizer 2020;
[0085] The dispersant is selected from at least one of vinyl bisstearamide, calcium stearate, and oxidized polyethylene wax.
[0086] It should be noted that in the buoy shell of the present invention, by selecting the above-mentioned antioxidants, ultraviolet absorbers, and light stabilizers, the buoy shell can have better anti-oxidation and ultraviolet resistance and good stability when used in harsh environments such as at sea.
[0087] In another embodiment of the above-mentioned environmentally friendly floating buoy of the present invention, the filler is expanded polystyrene;
[0088] The thickness of the buoy shell is 2 to 5 cm;
[0089] When the buoy shell is cylindrical, the ratio of height to diameter is 1-2:1, the height is 30-70 cm, and the diameter is 10-40 cm.
[0090] It should be noted that the environmentally friendly floating pontoon is not limited to the cylindrical shape, but can also be a variety of other shapes. The pontoon shell is a hollow cavity shape. The expanded polystyrene used as the filler has the characteristics of light weight (10-40g / L), low water absorption (the water absorption rate after long-term immersion in water is less than 10%), impact resistance, heat resistance, aging resistance, etc., and low cost, making it an ideal floating material. Because the interior is filled with expanded polystyrene, the intrusion of seawater is avoided, and buoyancy can be provided, which is equivalent to a complete plastic floating body. Therefore, even if a hole appears in the pontoon, it will not sink, ensuring the safety and effectiveness of the pontoon. By controlling the thickness of the pontoon shell and the size of the cylindrical pontoon shell as above, the floating pontoon can float stably on the water with good stability.
[0091] In another aspect, the present invention provides a method for preparing the above-mentioned environmentally friendly floating buoy, which comprises the following steps:
[0092] (1) Diphenyl carbonate and alkyl glycol HO-(CH2) m -OH is prepolymerized and transesterified in the presence of a catalyst to obtain polycarbonate 8≤m≤16;
[0093] (2) The following components in parts by weight are sequentially melted, plasticized, extruded, granulated, and processed into a hollow buoy shell:
[0094]
[0095] (3) Filling a filling body inside the buoy shell to obtain the environmentally friendly floating buoy.
[0096] It should be noted that in the method for preparing an environmentally friendly floating buoy of the present invention, a biodegradable polycarbonate (also referred to as a polyethylene-like substance) is firstly designed and prepared in step (1). The process is based on a melt transesterification reaction and aims to embed a sensitive ester bond into the CH main chain. Specifically, Figure 2 As shown, during the reaction of diphenyl carbonate 1 and alkyl glycol 2, phenol 3 is generated as a byproduct, and finally the target product polycarbonate 4 is obtained; in step (2), environmentally friendly raw material particles are obtained by melt extrusion granulation, and then the raw material particles are processed into a hollow buoy shell; in step (3), a filling body is filled in the inner cavity of the buoy shell to obtain the environmentally friendly floating buoy.
[0097] When preparing the floating buoy in the present invention, the polycarbonate prepared in step (1) The buoy shell is prepared by compounding with high-density polyethylene, low-density polyethylene, carbon fiber and other components in a certain ratio. The buoy shell can have excellent mechanical properties. When the buoy is damaged after floating for a long time at sea, the presence of carbon fiber and polycarbonate allows the buoy shell to be broken into a smaller structure, avoiding the long-term existence of a large-volume damaged shell structure, greatly reducing the entanglement and entanglement of the damaged shell structure on marine organisms, greatly reducing the direct harm to marine organisms, and the above-mentioned polycarbonate can be well degraded, and the impact of the buoy shell particles finally formed on the environment is also greatly reduced. Therefore, the floating buoy prepared by the present invention has environmentally friendly properties and can safely, stably and reliably provide buoyancy for photovoltaic modules.
[0098] In one embodiment of the above method of the present invention, steps (1) to (3) are performed as follows:
[0099] In step (1):
[0100] The alkyl glycol is 1,12-dodecanediol;
[0101] The catalyst is a phosphazene-based catalyst, preferably t-BuP2;
[0102] The weight ratio of the diphenyl carbonate, the alkyl glycol and the catalyst is 100:(105-110):(0.001-0.002);
[0103] The prepolymerization comprises:
[0104] Dissolving the diphenyl carbonate and the alkyl glycol in tetrahydrofuran under vacuum, then adding the catalyst and stirring at a constant temperature of 80 to 90° C. and a speed of 10 to 15 r / min for 2 to 4 hours to obtain a prepolymer product;
[0105] The transesterification comprises:
[0106] The prepolymer product is heated to 200-230° C. and subjected to reduced pressure distillation reaction for 10-12 hours, and then separated by sedimentation with n-hexane and then dried in vacuum to obtain the polycarbonate;
[0107] In step (2):
[0108] The hollow buoy shell is processed by blow molding;
[0109] In step (3):
[0110] The filling body is filled in the buoy shell by a pouring method or a spraying method.
[0111] It should be noted that, when preparing polycarbonate in step (1), the above-mentioned raw materials and catalysts are selected and the weight ratio and the reaction conditions of prepolymerization and ester exchange are controlled as above. The prepared polycarbonate can be better degraded, and the buoy shell obtained by compounding with components such as high-density polyethylene, low-density polyethylene, carbon fiber, etc. can obtain better comprehensive performance.
[0112] In step (3), the inner cavity of the buoy shell is filled with expanded polystyrene, which solves the buoyancy failure problem of the floating buoy at sea, ensures the effectiveness of the buoyancy of the buoy and the long-term stability of the offshore photovoltaic system without sinking; even if the buoy shell is damaged, the buoyancy failure will not occur due to the presence of the internal expanded polystyrene. In addition, the polystyrene material has excellent resilience, good absorption of impact and vibration energy, high strength, good thermal insulation, good environmental stability, low cost, easy to obtain, and has great economic benefits.
[0113] In short, the method of the present invention has simple production process, high production efficiency, low cost, convenient material acquisition, high efficiency, is suitable for mass production, and has extremely high environmental value.
[0114] The present invention is further described in detail by way of examples below, but the present invention is not limited thereto. In the following examples, unless otherwise specified, the experimental instruments and raw materials involved are all commercially available products.
[0115] Reagent source description:
[0116] (1) Reagent Description in Polycarbonate Preparation Example
[0117] Diphenyl carbonate was purchased from Aladdin with the product number D106411;
[0118] 1,12-Dodecanediol was purchased from Aladdin with the product number D135990;
[0119] The phosphazene-based catalyst t-BuP2 was purchased from Delta Biotech Ltd.
[0120] (2) Reagent description in the preparation example of composite carbon fiber
[0121] When the carbon fiber surface is treated with a vacuum plasma cleaning machine, the gas used is oxygen. The manufacturer of the vacuum plasma cleaning machine is FARI and the model is GD-5.
[0122] The diameter of the carbon fiber is 5.4 μm and the length is 6.0 mm;
[0123] Nano-silicon dioxide was purchased from Evonik, brand AEROSIL 200;
[0124] (3) Reagent Description in the Examples
[0125] The density of No. 1 high-density polyethylene is 0.952g / cm 3 , melt index (MI) (190℃ / 21.6kg) 4.5g / 10min;
[0126] The density of No. 2 high-density polyethylene is 0.949g / cm 3 , melt index (MI) (190℃ / 21.6kg) 5.6g / 10min;
[0127] The density of No. 3 high-density polyethylene is 0.953g / cm 3 , melt index (MI) (190℃ / 21.6kg) 5.1g / 10min;
[0128] Low-density polyethylene was purchased from Sabic, with a grade of R50035E and a density of 0.935 g / cm 3 , melt index (MI) (190℃ / 21.6kg) is 35g / 10min;
[0129] Expanded polystyrene is conventional expanded polystyrene particles purchased from Swire, brand F-4S;
[0130] Oxidized polyethylene wax was purchased from BASF, brand 62#;
[0131] The polycarbonate used in the following examples was prepared by the following polycarbonate preparation example.
[0132] <Polycarbonate Preparation Example>
[0133] 1) Figure 2 This is a technical route for the synthesis of biodegradable polycarbonate (new type of polyethylene), and its specific design formula is as follows (by weight, including the following components):
[0134] 100 parts of diphenyl carbonate
[0135] 1,12-Dodecanediol 105 parts
[0136] Phosphazene-based catalyst (t-BuP2) 0.0015 parts
[0137] 2) The operation steps are as follows:
[0138] a. Prepolymerization process
[0139] Diphenyl carbonate and 1,12-dodecanediol were fully dissolved in tetrahydrofuran in the above proportions under a vacuum environment of -0.1 MPa, and then a certain proportion of t-BuP2 was added. After mixing evenly, the mixture was stirred at a constant temperature, the temperature was set at 90°C, the rotation speed was 15 r / min, and the reaction time was 3 hours.
[0140] b. Transesterification process
[0141] After the reaction is completed, slowly heat to 230°C and perform vacuum distillation for 12 hours. It should be noted that the reaction is essentially a polycondensation reaction, and a small molecular intermediate phenol will be generated during the process. Therefore, the precipitation of phenol should be promoted as much as possible during vacuum distillation. Finally, n-hexane solvent is used to precipitate and separate the target product and vacuum dry it. The prepared polycarbonate is
[0142] <Composite Carbon Fiber Preparation Example 1>
[0143] (1) Preparation of surface activated carbon fiber: 100 g of carbon fiber was surface treated by a vacuum plasma cleaning machine, with a radio frequency of 27.12 kHz, a power of 65%, a cavity pressure of 110 Pa, and an oxygen flow rate of 5 cm 3 / min, spraying time 3min, take out and get it.
[0144] (2) Preparation of filler composite auxiliary powder (filler powder): 1 g of talcum powder, 2 g of carbon black and 2 g of nano-silicon dioxide mixed powder were ground and mixed in a ball mill, and then filtered through a 500-mesh sieve.
[0145] (3) Preparation of composite carbon fiber: Add the above-mentioned filler composite auxiliary agent powder and 2g of silane coupling agent KH550 into 150mL of anhydrous ethanol and disperse by ultrasonication to obtain a uniformly mixed impregnation solution, then ultrasonically vibrate the above-mentioned plasma-treated carbon fiber (surface activated carbon fiber) in the impregnation solution for 1h, take it out and dry it in a vacuum drying oven to obtain No. 1 composite carbon fiber.
[0146] <Composite Carbon Fiber Preparation Example 2>
[0147] (1) Preparation of surface activated carbon fiber: 100 g of carbon fiber was surface treated by a vacuum plasma cleaning machine, with a radio frequency of 27.12 kHz, a power of 80%, a cavity pressure of 110 Pa, and an oxygen flow rate of 5 cm 3 / min, spraying time 3min, take out and get it.
[0148] (2) Preparation of filler composite auxiliary powder (filler powder): 0.5 g of talcum powder, 2.5 g of carbon black and 3 g of nano-silicon dioxide mixed powder were ground and mixed in a ball mill, and filtered through a 500-mesh sieve.
[0149] (3) Preparation of composite carbon fiber: Add the above-mentioned filler composite auxiliary agent powder and 2.5g of silane coupling agent KH550 into 150mL of anhydrous ethanol and disperse by ultrasonication to obtain a uniformly mixed impregnation solution, then ultrasonically vibrate the above-mentioned plasma-treated carbon fiber (surface activated carbon fiber) in the impregnation solution for 1.5h, take it out and dry it in a vacuum drying oven to obtain No. 2 composite carbon fiber.
[0150] <Composite Carbon Fiber Preparation Example 3>
[0151] (1) Preparation of surface activated carbon fiber: 100 g of carbon fiber was surface treated by a vacuum plasma cleaning machine, with a radio frequency of 27.12 kHz, a power of 70%, a cavity pressure of 110 Pa, and an oxygen flow rate of 5 cm 3 / min, spraying time 5min, take out and get it.
[0152] (2) Preparation of filler composite auxiliary powder (filler powder): 0.5 g of talcum powder, 3 g of carbon black and 1.5 g of nano-silicon dioxide mixed powder were ground and mixed in a ball mill, and filtered through a 500-mesh sieve.
[0153] (3) Preparation of composite carbon fiber: Add the above-mentioned filler composite auxiliary agent powder and 1g of silane coupling agent KH550 into 150mL of anhydrous ethanol and disperse by ultrasonication to obtain a uniformly mixed impregnation solution, then ultrasonically vibrate the above-mentioned plasma-treated carbon fiber (surface activated carbon fiber) in the impregnation solution for 1h, take it out and dry it in a vacuum drying oven to obtain No. 3 composite carbon fiber.
[0154] <Comparative Example 1 for Preparation of Composite Carbon Fiber>
[0155] Composite carbon fibers were prepared according to the method in Composite Carbon Fiber Preparation Example 1, except that:
[0156] Without performing step (1), the plasma-treated carbon fiber (surface-activated carbon fiber) used in step (3) is replaced with carbon fiber that has not been plasma-treated, thereby finally obtaining composite carbon fiber No. 4.
[0157] <Comparative Example 2 for Preparation of Composite Carbon Fiber>
[0158] Composite carbon fibers were prepared according to the method in Composite Carbon Fiber Preparation Example 1, except that:
[0159] Omit step (2), perform step (1) and then perform step (3), in which 2 g of silane coupling agent KH550 is added to 150 mL of anhydrous ethanol and ultrasonically dispersed to obtain a uniformly mixed impregnation solution, and finally obtain No. 5 composite carbon fiber.
[0160] Example 1
[0161] <Preparation of buoy shell>
[0162] The flotation buoy shell was prepared using the following components by weight:
[0163]
[0164] The above components were added into a twin-screw extruder with a screw aspect ratio of 35 and an extruder temperature set at 230°C. After melting, plasticizing, extruding, and granulating, a hollow cylindrical buoy shell (diameter × height: 30 cm × 50 cm, thickness 3 cm) was prepared by a blow molding process.
[0165] <Preparation of floating buoy>
[0166] The floating buoy is obtained by filling the buoy shell with expanded polystyrene (just fill up the inner cavity) by the perfusion method.
[0167] Example 2
[0168] <Preparation of buoy shell>
[0169] The flotation buoy shell was prepared using the following components by weight:
[0170]
[0171]
[0172] The above components were added into a twin-screw extruder with a screw aspect ratio of 35 and an extruder temperature set at 230°C. After melting, plasticizing, extruding, and granulating, a hollow cylindrical buoy shell (diameter × height: 30 cm × 50 cm, thickness 3 cm) was prepared by a blow molding process.
[0173] <Preparation of floating buoy>
[0174] The floating buoy is obtained by filling the buoy shell with expanded polystyrene (just fill up the inner cavity) by the perfusion method.
[0175] Example 3
[0176] <Preparation of buoy shell>
[0177] The flotation buoy shell was prepared using the following components by weight:
[0178]
[0179] The above components were added into a twin-screw extruder with a screw aspect ratio of 35 and an extruder temperature set at 230°C. After melting, plasticizing, extruding, and granulating, a hollow cylindrical buoy shell (diameter × height: 30 cm × 50 cm, thickness 3 cm) was prepared by a blow molding process.
[0180] <Preparation of floating buoy>
[0181] The floating buoy is obtained by filling the buoy shell with expanded polystyrene (just fill up the inner cavity) by the perfusion method.
[0182] Comparative Example 1
[0183] The floating buoy was prepared according to the method in Example 1, except that:
[0184] When preparing the floating pontoon shell, the composite carbon fiber is replaced with carbon fiber.
[0185] Comparative Example 2
[0186] The floating buoy was prepared according to the method in Example 2, except that:
[0187] When preparing the floating pontoon shell, the No. 2 composite carbon fiber is replaced with the No. 4 composite carbon fiber.
[0188] Comparative Example 3
[0189] The floating buoy was prepared according to the method in Example 3, except that:
[0190] When preparing the floating pontoon shell, the No. 3 composite carbon fiber is replaced with the No. 5 composite carbon fiber.
[0191] Test Case
[0192] (1) The test results of the weight average molecular weight and molecular weight distribution coefficient of the polycarbonate prepared in the polycarbonate preparation example are shown in Table 1 below:
[0193] Table 1
[0194] Performance parameters result Test Method Weight average molecular weight / Mw 45000 GPC / GB / T 27843-2011 Molecular weight distribution index / PDI 0.75 GPC / GB / T 27843-2011
[0195] (2) The composite carbon fibers prepared in the composite carbon fiber preparation examples 1 to 3 were subjected to scanning electron microscopy analysis, wherein the SEM photo of the composite carbon fiber prepared in the composite carbon fiber preparation example 1 is shown in FIG. Figure 3 As shown, there are granular substances between the fibers, which are fillers composed of nano-silicon dioxide, talcum powder and carbon black, which are mixed with carbon fibers to form a similar "island structure". The fillers on the fiber surface have been well integrated with the fibers.
[0196] (3) The raw materials polycarbonate, high-density polyethylene, low-density polyethylene, composite carbon fiber (carbon fiber in Comparative Example 1), antioxidant, etc. used to prepare the floating buoy shell in Examples 1 to 3 and Comparative Examples 1 to 3 were melted, plasticized, extruded, and granulated to obtain pellets in accordance with the above-mentioned weight proportions. The test results of Examples 1 to 3 are shown in Table 2 below, and the results of Comparative Examples 1 to 3 are shown in Table 3 below.
[0197] Table 2
[0198]
[0199] Table 3
[0200]
[0201] The above results show that compared with Example 1, Comparative Example 1 uses ordinary carbon fiber to improve the toughness of the material, but lacks stress concentration points when subjected to force, so the elongation at break and environmental stress cracking resistance are poor. Comparative Example 2 shows that the carbon fiber whose surface is not plasma-treated cannot be compounded with fillers such as carbon black due to the lack of active groups, so it exhibits similar properties to Comparative Example 1. The environmental stress cracking resistance of Comparative Example 3 is greatly improved compared with Comparative Examples 1 and 2, but due to the uneven filler powder and uneven particle size in the system, the composite carbon fiber structure formed is unstable, so the optimal performance is still not achieved. Finally, it is explained that the composite particles prepared by the present invention have excellent environmental stress cracking resistance, weather resistance, higher strength, and better comprehensive mechanical properties. In addition, Example 2 further significantly improves the elongation at break and environmental stress cracking resistance of the pellets after granulation of the float shell raw material by cleverly controlling the weight ratio of polycarbonate to the total weight of high-density polyethylene and low-density polyethylene.
[0202] The present application has been described above in conjunction with preferred embodiments, but these embodiments are only exemplary and serve only as an illustration. On this basis, various replacements and improvements may be made to the present application, all of which fall within the scope of protection of the present application.
Claims
1. An environmentally friendly floating buoy, comprising a buoy shell and a filling body filled in the buoy shell; wherein: The buoy shell comprises the following components in parts by weight: The structural formula of the polycarbonate is 8≤m≤16.
2. The environmentally friendly floating buoy according to claim 1, wherein: The weight average molecular weight of the polycarbonate is 40,000 to 50,000, and the molecular weight distribution coefficient is 0.6 to 0.
8.
3. The environmentally friendly floating buoy according to claim 1, wherein: The weight ratio of the polycarbonate to the total weight of the high-density polyethylene and the low-density polyethylene is (42-45):
100.
4. The environmentally friendly floating buoy according to claim 1, wherein: The density of the high-density polyethylene is 0.945-0.97 g / cm 3 , melt index is 4-10g / 10min; The density of the low-density polyethylene is 0.91-0.94 g / cm 3 , the melt index is 30-50g / 10min.
5. The environmentally friendly floating buoy according to claim 1, wherein: The carbon fiber is a composite carbon fiber, which comprises carbon fiber, nano silicon dioxide, carbon black, talcum powder and a silane coupling agent.
6. The environmentally friendly floating buoy according to claim 5, wherein: The mass ratio of nano-silicon dioxide, carbon black, talcum powder and silane coupling agent in the composite carbon fiber is (0.5-5):(0.5-5):(0.1-3):(1-5); The carbon fiber has a length of 1 to 10 mm, preferably 4 to 8 mm, and a diameter of 1 to 10 μm, preferably 2 to 8 μm.
7. The environmentally friendly floating buoy according to claim 1, wherein: The antioxidant is selected from at least one of antioxidant 168, antioxidant 1010, and antioxidant 1076; The ultraviolet absorber is selected from at least one of UV-328, UV-329 and UV-327; The light stabilizer is selected from at least one of light stabilizer 770, light stabilizer 944, and light stabilizer 2020; The dispersant is selected from at least one of vinyl bisstearamide, calcium stearate, and oxidized polyethylene wax.
8. The environmentally friendly floating buoy according to claim 1, wherein: The filler is expanded polystyrene; The thickness of the buoy shell is 2 to 5 cm; When the buoy shell is cylindrical, the ratio of height to diameter is 1-2:1, the height is 30-70 cm, and the diameter is 10-40 cm.
9. A method for preparing the environmentally friendly floating buoy according to any one of claims 1 to 8, wherein: The steps include: (1) Diphenyl carbonate and alkyl glycol HO-(CH2) m -OH is prepolymerized and transesterified in the presence of a catalyst to obtain polycarbonate 8≤m≤16; The empty (floating 2) cylinder is used to melt, plasticize, extrude and granulate the components in parts by weight in sequence to form the shell. (3) Filling a filling body inside the buoy shell to obtain the environmentally friendly floating buoy.
10. The method according to claim 9, wherein: Perform steps (1) to (3) as follows: In step (1): The alkyl glycol is 1,12-dodecanediol; The catalyst is a phosphazene-based catalyst, preferably t-BuP2; The weight ratio of the diphenyl carbonate, the alkyl glycol and the catalyst is 100:(105-110):(0.001-0.002); The prepolymerization comprises: Dissolving the diphenyl carbonate and the alkyl glycol in tetrahydrofuran under vacuum, then adding the catalyst and stirring at a constant temperature of 80 to 90° C. and a speed of 10 to 15 r / min for 2 to 4 hours to obtain a prepolymer product; The transesterification comprises: The prepolymer product is heated to 200-230° C. and subjected to reduced pressure distillation reaction for 10-12 hours, and then separated by sedimentation with n-hexane and then dried in vacuum to obtain the polycarbonate; In step (2): The hollow buoy shell is processed by blow molding; In step (3): The filling body is filled in the buoy shell by a pouring method or a spraying method.